Paciente de sexo femenino de 50 años de edad con gota y obesidad grado 1. - Maigualca Tomala, Jenny Lissette (2021)
Gout has been associated with an increased risk of kidney, cardiovascular, dyslipidemia and diabetes mellitus, when accompanied by obesity it becomes a disabling disease that tends to degenerate the joints, also increasing the risk of cardiovascular diseases and strokes. The objective of this clinical case is to improve the nutritional status of the patient with gout and obesity through a dietotherapeutic treatment. Therefore, a patient with a diagnosis of gout of 10 years of evolution is described, the study collects pertinent bibliographic data, data from her medical history, complementary laboratory tests, evaluation of nutritional status, among others. These data served to determine the diagnosis that directed the treatment to be prescribed. The results obtained during a month of treatment report a slight improvement in the nutritional status of the patient who arrived at the nutritional consultation with a diagnosis of gout and obesity. This was achieved through dietotherapeutic treatment according to their nutritional needs.